2019
DOI: 10.1007/s00018-019-03206-1
|View full text |Cite
|
Sign up to set email alerts
|

Acute hydroxyurea-induced replication blockade results in replisome components disengagement from nascent DNA without causing fork collapse

Abstract: During S phase, replication forks can encounter several obstacles that lead to fork stalling, which if persistent 19 might result in fork collapse. To avoid this collapse and to preserve the competence to restart, cells have 20 developed mechanisms that maintain fork stability upon replication stress. In this study, we aimed to 21 understand the mechanisms involved in fork stability maintenance in non-transformed human cells by 22 performing an iPOND-MS analysis in hTERT-RPE cells under different replication s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
32
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 18 publications
(32 citation statements)
references
References 62 publications
0
32
0
Order By: Relevance
“…We therefore examined the effect of CST depletion on genomic ssDNA production after fork stalling. HeLa cells depleted of STN1 (Fig 2A) were treated with HU for 3 h, a condition that induced fork stalling and produced ssDNA (Ercilla et al ., 2019). Subsequently, BrdU staining was performed under the non‐denaturing condition to measure ssDNA amount.…”
Section: Resultsmentioning
confidence: 99%
“…We therefore examined the effect of CST depletion on genomic ssDNA production after fork stalling. HeLa cells depleted of STN1 (Fig 2A) were treated with HU for 3 h, a condition that induced fork stalling and produced ssDNA (Ercilla et al ., 2019). Subsequently, BrdU staining was performed under the non‐denaturing condition to measure ssDNA amount.…”
Section: Resultsmentioning
confidence: 99%
“…As shown in Figure 3B, OZF from nuclear extract co‐immunoprecipitated not only with Claspin (Figure 1), but also with Cdc45, MCM6, and MCM2, components of the CMG complex. Since chromatin‐bound Cdc45 is only found in activated (or fired) replication origins, 54 the presence of OZF at active forks was analyzed by iPOND, a method that allows the identification of proteins associated with newly synthesized DNA during ongoing replication 48 . Indeed, together with PCNA and Claspin, OZF is associated with nascent DNA, demonstrating the presence of OZF at active replisomes (Figure 3C).…”
Section: Resultsmentioning
confidence: 99%
“…One possible explanation for these observations is that vDNA synthesis proceeds more slowly in NG18 VRCs than in WT VRCs. Because RPA levels have been observed to increase at stressed replication forks in order to stabilize the extended stretches of ssDNA and initiate the DDR [53][54][55][56], we analyzed RPA32 localization at sites of NG18 vDNA synthesis. PCC analysis showed that the correlation of LT with dim RPA32 was significantly higher in NG18-infected cells than in WT-infected cells (Figs 5E and S5C, orange), possibly representing increased RPA-bound ssDNA and replication stress [53][54][55][56].…”
Section: St Contributes To Vdna Relocalization and Vrc Organizationmentioning
confidence: 99%